Synapse - James, Steven 1969- (Thorndike, Maine : Center Point Large Print, 2019)
Thirty years in the future. When Kestrel Hathaway, a pastor in Cincinnati, witnesses a terror attack, shes drawn into a world of conspiracies and lies that she and Jordan, her cognizant robot, have to untangle before its too late. With the help of counterterrorism agent Nick Vernon, she needs to stop a second, more brutal attack, that could leave thousands dead. And the clock is ticking.... -- adapted from back cover.
"From the critically-acclaimed author whom Publishers Weekly has called a "master storyteller" comes a taut new thriller where things are not always as they appear to be ... Thirty years from now, when Kestrel Hathaway, a pastor in Cincinnati, witnesses a terror attack, shes drawn into a world of conspiracies and lies that she and Jordan, her cognizant robot, have to untangle before its too late. With the help of counterterrorism agent Nick Vernon, she needs to stop a second, more brutal attack, that could leave thousands dead. And the clock is ticking. Deftly weaving suspense and intrigue into a rich, resonant tale that explores faith and what it really means to be human, James offers us a glimpse into the future and into our own hearts. Synapse is an unforgettable, gripping story of dreams shattered, truth revealed, and hope reborn"--
Keywords: Twenty-first century -- Forecasts; Fiction; Robots -- Fiction; Artificial intelligence -- Fiction; Cyborgs; Fiction; Terrorism -- Prevention; Fiction; Government investigators; United States; Fiction; Women clergy -- United States; Fiction; Eschatology; Fiction; Large type books; Cincinnati (Ohio) -- Fiction; Christian fiction; Thrillers (Fiction); Science fiction